Training and work process in Multiprofessional Residency in Health as innovative strategy - Mariana da Silva Bernardo; Greici Capellari Fabrizzio; Marina Leite Souza; Thiago Oliveira dos Santos; Selma Regina de Andrade (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objectives: To reflect about education in health and work process on three programs of multiprofessional residency in Florianópolis/SC. Method: Reflexive study about Multiprofessional Residency Health Programs of Florianópolis. Results: Multiprofessional Residency characterizes training health professionals through service education. Developing these professionals' specialization with assignments that promote professional exercise and magnifies multiprofessional work at the same time, for excellency in unabridged healthcare. Final Considerations: Multiprofessional Residency Programs make interdisciplinary education, sharing knowledge between residents and other professionals stimulating development of innovation skills.